(untitled) (Global Journal of Science Frontier Research, 2018)
The study was conducted at Mareko Woreda to undertake red pepper value chain analysis and examine the factors that affect the supply of red pepper. The area is known for its surplus production of red pepper. The study has focused on the market channel, conduct, performance of red pepper markets and the main constraints of volume of red pepper supply. Structured questionnaire, focus group discussions, key informant interviews and field observation were used for generating the data. The channel in which, retailers buy red pepper directly from farmers and they in turn sell the red pepper directly to the consumer’s outlooks as the 1st important channel in the study area in terms of volume transacted. About 78.3% of the red pepper producers sold the red pepper by the price set of both parties based on negotiation. With regard to the payment strategy, about 79.17 % of sample farmers sold their product on cash. Traders took a total of 87.75% out of the total profit margin; specifically, among traders, processors profit margin constitutes the highest share (30.71%) followed by retailors (20.49%). The result from the econometric analysis show that, education level of the household head, Average lagged price, Proportion of land allocated for red pepper production, experience of the house hold head were found to have positive influence on marketable supply of red pepper. Likewise, Average input price and diseases were found to influence marketable supply of negatively.